Pharmacognostic and Preliminary Phytochemical Evaluation of the leaves of Asparagus Racemosus Willd - Md. Usman, Md. Rageeb; P. Vadnere, Gautam P. Vadnere; Ravindra Mandage, Utkarsh (Journal of Neonatal Surgery, 2025)
This study looks closely at the leaves of Asparagus racemosus Willd. This plant is commonly used in Ayurveda. We focus on its pharmacognostic and early phytochemical properties. The tuberous roots are well-known for their healing properties, but the leaves are mostly unexplored. The study focused on the shape, structure, and chemical properties of the leaves. It aimed to confirm their authenticity and purity for use in medicine. The pharmacognostic assessment looked at three areas: organoleptic, microscopic, and physicochemical analyses. It highlighted important features such as lignified fibers, stomata, epidermal palisade cells, and calcium oxalate crystals. These details help confirm plant identity. Quantitative microscopic evaluations, including stomatal index (4.25), palisade ratio (5.75/mm²), and phloem fiber width (12.5–68μ), provide key identifiers for the plant material. Physicochemical studies showed total ash at 10.47%. Acid-insoluble ash was found at 1.34%. The water-soluble extractive value was high at 28.86%. These results suggest a strong presence of bioactive compounds. Phytochemical screening showed flavonoids, glycosides, alkaloids, and tannins. This confirms the leaves' therapeutic potential. The high extractive values indicate that both water and alcohol extracts contain many bioactive compounds. These findings help standardize and validate Asparagus racemosus leaves for medicine. The study provides important baseline data for using these herbs in formulations. This highlights their significance in pharmacology.